Gene expression plasticity, genetic variation and fatty acid remodelling in divergent populations of a tropical bivalve species. Issue 6 (24th April 2022) - Le Luyer, Jérémy; Monaco, Cristian J.; Milhade, Léo; Reisser, Céline; Soyez, Claude; Raapoto, Hirohiti; Belliard, Corinne; Le Moullac, Gilles; Ky, Chin‐Long; Pernet, Fabrice
Abstract: Ocean warming challenges marine organisms' resilience, especially for species experiencing temperatures close to their upper thermal limits. A potential increase in thermal tolerance might significantly reduce the risk of population decline, which is intrinsically linked to variability in local habitat temperatures. Our goal was to assess the plastic and genetic potential of response to elevated temperatures in a tropical bivalve model, Pinctada margaritifera . We benefit from two ecotypes for which local environmental conditions are characterized by either large diurnal variations in the tide pools (Marquesas archipelago) or low mean temperature with stable to moderate seasonal variations (Gambier archipelago). We explored the physiological basis of individual responses to elevated temperature, genetic divergence as well as plasticity and acclimation by combining lipidomic and transcriptomic approaches. We show that P. margaritifera has certain capacities to adjust to long‐term elevated temperatures that was thus far largely underestimated. Genetic variation across populations overlaps with gene expression and involves the mitochondrial respiration machinery, a central physiological process that contributes to species thermal sensitivity and their distribution ranges. Our results present evidence for acclimation potential in P. margaritifera and urge for longer term studies to assess populations resilience in the face of climate change. Abstract : A puzzling question in molecular ecology and conservation is how to assess the capacities of populations to cope with predicted climate changes. This study is one of the few to incorporate thermal gradient and the combined exploration of molecular and physiological responses which will benefit to the field of eco‐physiology. Résumé: Le réchauffement des océans remet en question la résilience des organismes marins, en particulier pour les espèces connaissant des températures proches de leurs limites thermiques supérieures. Une augmentation potentielle de la tolérance thermique pourrait ainsi réduire considérablement le risque de déclin de la population. L'objectif de cette étude était d'évaluer le potentiel plastique et génétique de la réponse à l'exposition courte et chronique à températures élevées chez une espèce de bivalve tropical, Pinctada margaritifera . Ce modèle bénéficie de l'existence de deux écotypes pour lesquels les conditions environnementales locales sont caractérisées soit par de fortes variations diurnes associées aux marées (archipel des Marquises) soit par une température moyenne plus basse et des variations saisonnières prononcées (archipel des Gambier). Nous avons exploré les bases physiologiques des réponses individuelles ainsi que la divergence génétique et quantifié la plasticité en combinant des approches lipidomique et transcriptomique. Nous montrons que P. margaritifera possède des capacités d'acclimatation à des températures élevées sur le long terme jusqu'à présent largement sous‐estimées. La divergence génétique entre populations est par ailleurs associée à des différences d'expression des gènes et implique la machinerie respiratoire mitochondriale, un processus physiologique central qui contribue à la sensibilité thermique des espèces et à leurs répartitions. Nos résultats présentent les bases des potentiels d'acclimatation chez P. margaritifera et soulignent l'importance d'études à plus long terme pour évaluer la résilience des populations face au changement climatique.